PENERAPAN KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DAN KURIKULUM 2013 (K-13) DALAM PELAJARAN IPA DI SMP SE-DISTRIK JAYAPURA SELATAN DAN DISTRIK ABEPURA KOTA JAYAPURA - SINCE, SINCE; SIREGAR, TIURLINA (Jurnal Ilmu Pendidikan Indonesia, 2018)
Have did a research of Implementation of Educational Unit Level Curriculum and Curriculum of 2013. In Science Education of Junior Elementary School at Se-District of North Jayapura and Abepura District in Jayapura Municipality. This research aimed to know about the implementation, the differences in implementation, the obstacle and solution between implementation of Educational Unit Level Curriculum and Curriculum of 2013, the result of implementation analysis will be refer to standardization that have been defined of Permendikbud as a reference in Curriculum of 2013 implementation. The type of this research is qualitative research. The method or technique of collecting data is interactive and non-interactive. The samples are all of Junior High School in Distrik Jayapura Selatan and Distrik Abepura Jayapura City which Implementation Educational Unit Level Curriculum and Curriculum of 2013. The result of research on Science Education learning process that supported by teacher’s questionnaire (1) The Process of learn planning, the level of success is 84% for Educational Unit Level Curriculum and 87% for Curriculum of 2013 (2) Implementation of the learning process, the level of success is 88% for Educational Unit Level Curriculum and 89% for Curriculum 2013 (3) The Learning Assessment, the level of success is 74% for Educational Unit Level Curriculum and 83% for Curriculum 2013 (4) The assessment to the result of Learning, the level of success is 81% for Educational Unit Level Curriculum and 87% for Curriculum 2013. Supervision of the process of learning is a good. Aplication of difference on: 1) Standars of contents; 2) Standars process; 3) Default judgment; 4) the use of the media. Contraints in the implementation of Educational Unit Level Curriculum and Curriculum of 2013: Human resources (HR), power support, integration of lessons (thematic/integrated).